Correlation of Climate Factors, Population Density, and Larva Free Rate (ABJ) on the Incidence of Dengue Hemorrhagic Fever (DHF) in Kendari City Period 2012-2021 - Fifi Nirmala; Nur S Layaly; La Ode Liaumin Azim (MEDULA JURNAL ILMIAH FAKULLTAS KEDOKTERAN UNIVERSITAS HALU OLEO, 2022)
Background: Dengue Hemorrhagic Fever (DHF) is an infectious disease that is endemic in most tropical areas in the world and around 3.5 billion people live in areas where dengue is endemic. A large number of individuals residing in a certain area will facilitate the spread of dengue disease and accelerate the transmission of dengue virus from vectors. Climate is very important for the survival of the Aedes Aegypti mosquito because mosquito breeding sites will increase along with climate change. ABJ shows the density of larvae in an area. Purpose(s): This study aimed to determine the correlation of climate factors, population density, and larva free rate (ABJ) to the incidence of Dengue Hemorrhagic Fever (DHF) in Kendari City in 2012–2021. Methods: This research method was a cross sectional design and Spearman rank correlation analysis using SPSS application. The data used are secondary data in the form of data on rainfall, humidity, temperature, population density, and the incidence of DHF in a period of 10 years (2012-2021) and ABJ in a period 2016 - 2020. Results: The results of this study indicated that the rainfall variable (p value = 0,000, r = 0,416) and the humidity variable (p value = 0,000, r = 0,446) have a sufficient and unidirectional correlation coefficient to the incidence of DHF in Kendari City in 2012-2021, ABJ variable (p value = 0,014, r = -0,949) has a very strong and non-unidirectional correlation coefficient on the incidence of DHF in Kendari City in 2016-2020, and there is no correlation between the temperature variable (p value = 0,087) and the variable population density (p value = 0,651) with the incidence of DHF in Kendari City in 2012-2021. Conclusion: There was a correlation between rainfall and humidity variables on the incidence of DHF in Kendari City in 2012-2021, there was a correlation between the ABJ variable and the incidence of DHF in Kendari City in 2016-2020, and there wasn’t a correlation between temperature variable and population density variable on the incidence of DHF in Kendari City in 2012-2021.